The drivers of employee engagement in multinational enterprise in manufacturing and service industry in Malaysia - Ho, Wen Huey (2019)
The main objective of this research was to study the relationships of core self-evaluations, leadership, information and communication, and rewards and recognition toward employee engagement in manufacturing and service industry in multinational enterprise in Malaysia. Employee engagement is an important aspect in an organization due to its influence on organization performance. Employee especially top talent turnover rate was increasing in this contemporary business environment due to lack of engagement in their organization. The data of this research had been collected by using survey questionnaires with closed-ended question and five point Likert scale. There are 223 sets of questionnaires have been distributed to the employees of MNE in Klang Valley are and there are only 200 sets of valid questionnaires can be analysed by using the Statistical Package for Social Science (SPSS). The results of the research are beneficial for both employers and employees to understand what is the major drivers of employee engagement in manufacturing and service industry in MNE. Besides, limitation and recommendations also have been suggested for other researchers in the future.